2005
DOI: 10.1007/s00467-004-1720-9
|View full text |Cite
|
Sign up to set email alerts
|

IgA deficiency and membranous glomerulonephritis presenting as nephrotic syndrome

Abstract: Selective IgA deficiency associated with glomerulonephritis is rare and no previous reports in childhood have been made of the association of IgA deficiency and membranous glomerulonephritis (MGN). We report a 5-year-old boy with selective IgA deficiency and MGN. He presented with nephrotic syndrome. Percutaneous renal needle biopsy showed diffuse global thickening on light microscopy and heavy IgG and moderate C3 deposits were found on immunofluorescence. Electron microscopy detected extensive global subepith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In children, secondary causes of MN have been associated with conditions such as systemic lupus erythematosus (SLE), hepatitis B or C infection, secondary and congenital syphilis, malaria, and Ebstein Barr Virus (EBV) infection [1, 6, 7]. Other rare underlying causes are C4 deficiency, selective IgA deficiency, or antitubular basement membrane antibodies [8–10].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…In children, secondary causes of MN have been associated with conditions such as systemic lupus erythematosus (SLE), hepatitis B or C infection, secondary and congenital syphilis, malaria, and Ebstein Barr Virus (EBV) infection [1, 6, 7]. Other rare underlying causes are C4 deficiency, selective IgA deficiency, or antitubular basement membrane antibodies [8–10].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The authors underlined the importance to detect IgAD in patients with renal diseases because they frequently require blood transfusion and may experience anaphylactic reactions. Kawasaki et al presented a 5-year-old boy with a primary nephrotic syndrome and IgAD (IgA less than 5 mg/dL) [14]. Oral prednisolone (2 mg kg/day) was started, and the proteinuria became negative at after 14 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Sirs, I read with interest the article in this journal entitled "IgA deficiency and membranous glomerulonephritis presenting as nephrotic syndrome" by Kawasaki et al [1]. The authors suggested that an increased level of circulating immune complexes was involved in the pathogenesis of membranous glomerulonephritis (MGN) in patients with IgA deficiency [1].…”
mentioning
confidence: 97%
“…The authors suggested that an increased level of circulating immune complexes was involved in the pathogenesis of membranous glomerulonephritis (MGN) in patients with IgA deficiency [1]. However, the renal biopsy of the patient described by Kawasaki et al demonstrated diffuse and global thickening of the glomerular capillary walls in the absence of any mesangial changes, mesangial deposition of immunoglobulin or complements or mesangial electron-dense deposits, findings that are compatible with idiopathic MGN [2].…”
mentioning
confidence: 98%
See 1 more Smart Citation